Minimal State-Space Realizations of Convolutional Codes - Pinho, T (2015)
In this work the minimality of state-space realizations of an input/output operator (encoder) and of the corresponding output behavior (code) are analyzed. Moreover, a procedure to obtain a minimal realization of a convolutional code starting from a minimal realization of an encoder of the code is provided.